Burnout and associative emotional status and coping style of healthcare workers in COVID-19 epidemic control: A cross-sectional study - Cece Yang; Xunqiang Wang; Xing Zhang; Wenping Liu; Chengmin Wang (Frontiers Media S.A., 2023)
ObjectiveThe aim of this study was to evaluate the prevalence of burnout, clinical anxiety, depression, and insomnia and to estimate the associations of adverse emotional status, coping style, and level of self-efficacy with burnout of healthcare workers in the Shenzhen Longgang District Frontline District Headquarters of COVID-19 epidemic control, China.MethodsIn this cross-sectional study, 173 staff completed the anonymous questionnaires of the Maslach Burnout Inventory, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-item Scale (GAD-7), Insomnia Severity Index (ISI), General Self-efficacy Scale, and Simplified Coping Style Questionnaire electronically (https://www.wjx.cn/) in June 2022. Hierarchical logistic regression was used to explore the associated factors of burnout in this study.ResultsThe prevalence of burnout in our participants (defined as high emotional exhaustion or high depersonalization) was 47.40%, and reduced personal accomplishment was 92.49%. The prevalence of clinically significant depression (the cutoff score of ≥15), anxiety (the cutoff score of ≥10), and insomnia (the cutoff score of ≥15) was 11.56, 19.08, and 19.08%, respectively. There was a degree of overlap between burnout and other measures of adverse mental status, most notably for anxiety (odds ratio, 27.049; 95% CI, 6.125-117.732; p < 0.001). Hierarchical logistic regression demonstrated that burnout was strongly associated with anxiety (OR = 23.889; 95% CI, 5.216-109.414; p < 0.001) and negative coping style (OR = 1.869; 95% CI, 1.278-2.921; p < 0.01) independently.ConclusionMedical staff involved in COVID-19 epidemic control in the post-epidemic era were at high risk of burnout, and most of them were in low personal accomplishment. Reducing anxiety and improving coping style by medical management institutions from the system level may be effective in alleviating burnout in healthcare workers.